Earthquakes and engineers : an international history - Reitherman, Robert, 1950- (ASCE Press, 2012)
This book is the first comprehensive treatment of the engineering techniques devised around the world to address seismic problems. Beginning in ancient times, threading through the Renaissance, and continuing into the latter half of the 20th century, this author traces the evolution of humankind's understanding of the cause and characteristics of earthquakes and the development of methods to design structures that resist seismic shocks. This book examines the responses not only of structural engineers, but also of geotechnical engineers, architects, and planners. International efforts in such countries as Japan, China, India, Chile, Turkey, Italy, and the United States are placed in the broader social, technological, and economic contexts of their eras. This highly readable book is an essential reference for civil engineers who work on projects in seismic regions. For researchers in the field of the history of science and technology, the book presents original source material and an extensive list of references. Written in a straightforward style that is accessible to nonengineers, it will also be valuable to architects, planners, officials, and social scientists. -- Provided by publisher.
Keywords: Earthquake engineering -- History.; elektronické knihy; electronic books